1999
DOI: 10.1007/s001099900038
|View full text |Cite
|
Sign up to set email alerts
|

The biology of the 17–1A antigen (Ep-CAM)

Abstract: The glycoprotein recognized by the monoclonal antibody (mAb) 17-1A is present on most carcinomas, which makes it an attractive target for immunotherapy. Indeed, adjuvant treatment with mAb 17-1A did successfully reduce the 5 years mortality among colorectal cancer patients with minimal residual disease. Currently the antibody is approved for clinical use in Germany, and is on its way to approval in a number of other countries. New immunotherapeutic strategies targeting the 17-1A antigen are in development or e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
449
1
10

Year Published

2001
2001
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 490 publications
(471 citation statements)
references
References 59 publications
10
449
1
10
Order By: Relevance
“…Binding studies with truncated Ep-CAM showed that both 323/A3 and edrecolomab do bind the immunodominant EGFlike domain I of Ep-CAM. 10,24 We infer from the competition data that M79 and MT201 also recognized this subdomain, although this conclusion may require further support from binding studies using truncated Ep-CAM versions.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…Binding studies with truncated Ep-CAM showed that both 323/A3 and edrecolomab do bind the immunodominant EGFlike domain I of Ep-CAM. 10,24 We infer from the competition data that M79 and MT201 also recognized this subdomain, although this conclusion may require further support from binding studies using truncated Ep-CAM versions.…”
Section: Discussionmentioning
confidence: 85%
“…5,6 Murine IgG2a is the functional equivalent of human IgG1, which to some extent can also exhibit ADCC and CDC with human effector cells and human complement, respectively. Edrecolomab was obtained by immunization of mice with human colon cancer cells and recognizes the pan-epithelial differentiation antigen Ep-CAM, [7][8][9][10] which is widely involved in homotypic cell adhesion of epithelial cells. Since then, numerous clinical trials have been undertaken with edrecolomab and other Ep-CAM-specific murine, chimeric and humanized monoclonal antibodies of various affinities.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Epithelial cell adhesion molecule (also referred to as 17-1A, KSA, GA733-2 or ESA) is a 40 kDa transmembrane glycoprotein that is expressed at relatively low levels on basolateral cell surfaces of most human simple epithelia (Balzar et al, 1999). Expression of Ep-CAM is highest during embryogenesis and in association with metaplastic or neoplastic changes, and lowest in mature epithelial tissues.…”
mentioning
confidence: 99%
“…This antigen is believed to be involved in homotypic calciumindependent cell-cell adhesion, as one of several classes of intercellular adhesion molecules [2]. Additional studies demonstrated Ep-CAM colocalization with the intracellular actin cytoskeleton, and also found that selective mutational analysis of the cytoplasmic domain resulted in lack of adhesion [3].…”
Section: Introductionmentioning
confidence: 96%